The impact of abiotic factors on daily spawning migration of Atlantic salmon (Salmo salar) in two north Swedish rivers - Holmsten, Anton (2015)
Atlantic salmon (Salmo salar) depends on two major migrations to fulfil their life cycle, from their birth place in rivers to sea, and back upstream the river again to spawn. Salmon stocks have been heavily reduced during the last century due to human activities such as hydropower and timber floating. Construction of fish ladders and restoration of rivers are recent management actions taken aiming at improving the remaining salmon stocks. Salmon are monitored during their migrations to get information on the stock status. This study focused on how environmental factors correlated with adult salmon upstream spawning migration data from two rivers in northern Sweden, Västerbotten County, Umeälven and Byskeälven. Salmon data from both rivers were obtained from fish counters placed in fish ladders. The fish ladder in river Umeälven was equipped with two VAKI fish counters, and salmon data from 2010-2013 was used. Salmon data from 2009-2013 from river Byskeälven were used, the fish ladder was equipped with a PORO fish counter 2009-2012, and a VAKI fish counter 2013. There were three questions that led the study; (I) which environmental variables can explain the daily variations in salmon upstream migration? (II) Are there any major differences between the factors influencing salmon spawning migration in an exploited river compared to an unexploited river? (III) Can an environmental factor be of greater or less importance for salmon upstream migration during the first and the last half of the season? Stepwise linear regressions were used to create models to find how the environmental factors correlated with salmon upstream migration. Both rivers had a seasonal migration pattern with most of the salmon migrating early in the season. Water flow had most influence on the salmon upstream migration in the studied rivers. There was a difference in which environmental factors had most influence on salmon migration between the first and second 50 % of migrating salmon in river Byskeälven. Adjusted Julian day number explained most of the migration in the best model for the migration first half of the season. Water temperature, water flow, and adjusted Julian day number explained the migration in the second half of the season.